Predictors of clinical outcomes in space-occupying cerebellar infarction undergoing suboccipital decompressive craniectomy - Lucia, Kristin; Reitz, Sarah; Hattingen, Elke; Steinmetz, Helmuth; Seifert, Volker; Czabanka, Marcus (Frontiers in Neurology, 2023)
Introduction: Despite current clinical guidelines recommending suboccipital decompressive craniectomy (SDC) in cerebellar infarction when patients present with neurological deterioration, the precise definition of neurological deterioration remains unclear and accurate timing of SDC can be challenging. The current study aimed at characterizing whether clinical outcomes can be predicted by the GCS score immediately prior to SDC and whether higher GCS scores are associated with better clinical outcomes. Methods: In a single-center, retrospective analysis of 51 patients treated with SDC for space-occupying cerebellar infarction clinical and imaging data were evaluated at the timepoints of symptom onset, hospital admission and preoperatively. Clinical outcome was measured by mRS. Preoperative GCS scores were stratified into three groups (GCS 3-8, 9-11 and 12-15). Univariate and multivariate Cox regression analysis were performed using clinical and radiological parameters as predictors of clinical outcome. Results: Cox-regression analysis GCS scores of 12-15 were significant predictors of positive clinical outcomes (mRS 1-2). For GCS scores of 3-8 and 9-11, no significant increase of proportional hazard ratios was observed. Negative clinical outcomes (mRS 3-6) were associated with infarct volume above 6.0 cm3, tonsillar herniation, brainstem compression and preoperative GCS score of 3-8 (HR 2.386 [CI 1.160-4.906]; p=0.018). Conclusions: SDC should be considered in patients with infarct volumes above 6.0 cm3 and with GCS between 12-15, as these patients may show better long-term outcome than those in which surgery is delayed until a GCS score below 11.